A meaning of branding: factors that influence purchase intention for food and beverage products SMEs - Mala, Iva Khoiril; Muhammad, Naufal Dzakwana; Saptaria, Lina; Anam, Choirul; Deuraseh, Nurdeng (Manajemen dan Bisnis, 2026)
The purpose of this study is to reveal various factors that influence the interest in purchasing Islamic-based food and beverage products, considering that the majority of Indonesia's population is Muslim, supported by a sustainable system for all food and beverage products that are required to have halal certification, which can have a major impact on whether or not people are interested in consuming Islamic-based products. The analysis method uses a quantitative method, namely SEM-PLS, it is stated that related factors that can influence consumer purchasing interest are product quality, social media marketing supported by brand trust and brand image that can influence it mediatingly. The population of this study is followers and the sample of this study is 359, while the sampling technique used is proportional random sampling. In addition, other factors such as Islamic branding can also strengthen the increase in consumer purchasing interest to ensure that products produced through Islamic products are in accordance with Islamic religious law and are guaranteed halal.